PREPARATION AND ANALYTICAL STUDY OF VATA GAJENDRA SINGH RASA (International Journal of Ayurveda and Pharma Research, 2016)
Rasaushadhis (Herbomineral preparations) are unique, acts in low dose, highly potent, dont have annoying taste and gives quick results, hence have edge over the herbal medicines. In the present trend of commercialization, there are many doubts raised regarding authenticity of Ayurvedic products. Hence analysis and assessment of raw material, different processes of drug preparation and final product is necessary to maintain authenticity, quality and purity of drug. At present time Amavata and Vatavyadhi are most common problem due to lifestyle change, changed food habits, lack of exercise etc. Vata Gajendra Singh Rasa is a Kharaliya Rasayana mentioned in Bhaishajyaratnawali under Amavata Rogadhikara. The main ingredients of Vata Gajendra Singh Rasa are Abhraka Bhasma, Loha Bhasma, Tamra Bhasma, Naga Bhasma, Kajjali and Vatsanabha. In this study Vata Gajendra Singh Rasa is prepared as per text of Bhaishajyaratnavali and assessment of drug done as per Ayurvedic and modern criteria. Chemical analytical studies carried out at government approved quality control laboratory. Analysis of main ingredients like Abhraka, Loha, Tamra, Naga, Vatsanabha, Parada and Gandhakadone by methods mentioned Ayurvedic Pharmacopoeia of India. In process analytical studies like analysis of the Bhasmas carried out as per methods of Ayurvedic Pharmacopoeia of India and evaluated with the standards mentioned in Pharmacopoeial Standards for Ayurvedic Formulations of Central Council for Research in Ayurveda and Siddha. Analytical tests of the final product (Vata Gajendra Singh Rasa pills) carried out as per reference of Ayurvedic Pharmacopoeia of India and Indian pharmacopoeia. Results of the raw material study justifies authenticity of raw material, results of in process study of the Bhasma are compared with standards, fulfills assessment criteria. Results of the final product discussed and conclusions are drawn, explained in full paper. Further studies are required to develop standards for the formulation.